Learning Management PAI Based on E-Learning at University - Hadi, Samsul; Sariman, Sariman; Khasanudin, Mohamad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The development of science and technology has a positive impact on the world of education. Various types of learning media, such as computers and internet networks, are the key to implementing e-learning learning. This study uses a qualitative descriptive approach. This study aims to describe and analyze the planning, implementation, and evaluation of e-learning-based learning. The results of the research are 1. Planning for PAI learning management based on e-learning at Billfath University Lamongan through creating student and lecturer accounts teachers designing PAI learning based on E-Learning by preparing Semester Implementation Plans (RPS), developing learning materials.2. Implementing E-Learning-Based PAI Learning activities at Billfath University Lamongan include registration of E-Learning accounts for lecturers and students, E-Learning learning process 3. Controlling E-Learning-based PAI learning at Billfath University Lamongan through formative, summative, and formative evaluations, the lecturer gave the task to the students to conclude the material on the methodology of Islamic Religious Education by using an oral test. At the same time, the summative evaluation is carried out at the end of the semester, namely the mid-semester examination (UTS) and the final semester examination (UAS). Controlling E-Learning-based PAI learning at Billfath University Lamongan through an evaluation of the formative method. The lecturer assigns students a task to conclude the methodology of Islamic Religious Education by using an oral test.